Nebulized PPARγ Agonists: A Novel Approach to Augment Neonatal Lung Maturation and Injury Repair - Morales, Edith (2014)
BACKGROUND: By stimulating lipofibroblast maturation, parenterally administered PPARγ agonists promote lung homeostasis and injury repair in the neonatal lung. In this study, we determined whether PPARγ agonists could be delivered effectively via nebulization to neonates, and whether this approach would also protect against hyperoxia-induced lung injury. METHODS: One-day old Sprague-Dawley rat pups were administered PPARγ agonists rosiglitazone (RGZ, 3 mg/kg), pioglitazone (PGZ, 3 mg/kg), or the diluent, via nebulization every 24h; animals were exposed to 21% or 95% O(2) for up to 72h. Twenty-four and 72h following initial nebulization, the pups were sacrificed for lung tissue and blood collection to determine markers of lung maturation, injury repair, and RGZ and PGZ plasma levels. RESULTS: Nebulized RGZ and PGZ enhanced lung maturation in both males and females, as evidenced by the increased expression of markers of alveolar epithelial and mesenchymal maturation. This approach also protected against hyperoxia-induced lung injury, since hyperoxia-induced changes in bronchoalveolar lavage cell and protein contents and lung injury markers were all blocked by nebulized PGZ. CONCLUSIONS: Nebulized PPARγ agonist administration promotes lung maturation and prevents neonatal hyperoxia-induced lung injury in both males and females.